2013
DOI: 10.1152/ajpendo.00036.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary copper supplementation restores β-cell function of Cohen diabetic rats: a link between mitochondrial function and glucose-stimulated insulin secretion

Abstract: β-Cell mitochondrial dysfunction as well as proinflammatory cytokines have been suggested to contribute to reduced glucose-stimulated insulin secretion (GSIS) in type 2 diabetes. We recently demonstrated that Cohen diabetic sensitive (CDs) rats fed a high-sucrose, low-copper diet (HSD) developed hyperglycemia and reduced GSIS in association with peri-islet infiltration of fat and interleukin (IL)-1β-expressing macrophages, whereas CD resistant (CDr) rats remained normoglycemic on HSD. We examined: 1) the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…Moreover, treatment with the iNOS inhibitor N -nitro-L-arginine prevented the IL-1␤-induced COX inhibition and GSIS reduction in isolated islets, whereas copper supplementation in vivo prevented the increase in iNOS expression and the development of hyperglycemia. These findings are reinforced by our previous studies showing that IL-1␤-expressing macrophages infiltrating the exocrine pancreas of hyperglycemic CDs rats reduce COX activity and ␤-cell function, both of which were reversed by copper supplementation (48,49). Thus, taken together, our previous and current data confirm the role of NO in IL-1␤-mediated GSIS reduction by reducing COX activity below a certain critical level.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Moreover, treatment with the iNOS inhibitor N -nitro-L-arginine prevented the IL-1␤-induced COX inhibition and GSIS reduction in isolated islets, whereas copper supplementation in vivo prevented the increase in iNOS expression and the development of hyperglycemia. These findings are reinforced by our previous studies showing that IL-1␤-expressing macrophages infiltrating the exocrine pancreas of hyperglycemic CDs rats reduce COX activity and ␤-cell function, both of which were reversed by copper supplementation (48,49). Thus, taken together, our previous and current data confirm the role of NO in IL-1␤-mediated GSIS reduction by reducing COX activity below a certain critical level.…”
Section: Discussionsupporting
confidence: 88%
“…In our previous in vivo study, low-copper HSD induced hyperglycemia in CDs rats, whereas coppersupplemented HSD reversed these phenomena (48,49). Our current ex vivo experiments on isolated islets of rats fed copper-supplemented HSD as well as in vitro coincubation of islets with the complex Cu-GHL (44) and IL-1␤ revealed that COX activity and GSIS similarly recovered upon copper supplementation.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations